2017
DOI: 10.1186/s12866-017-0951-4
|View full text |Cite
|
Sign up to set email alerts
|

Signature-tagged mutagenesis screening revealed a novel smooth-to-rough transition determinant of Salmonella enterica serovar Enteritidis

Abstract: Background Salmonella enterica serovar Enteritidis (S. Enteritidis) has emerged as one of the most important food-borne pathogens for humans. Lipopolysaccharide (LPS), as a component of the outer membrane, is responsible for the virulence and smooth-to-rough transition in S. Enteritidis. In this study, we screened S. Enteritidis signature-tagged transposon mutant library using monoclonal antibody against somatic O9 antigen (O9 MAb) and O9 factor rabbit antiserum to identify novel genes that are involved in smo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…It has been described that some LPS deficient mutants ( waaJ, waaL, rfaH, rfbH, rfbG, et al .) were used in Salmonella DIVA vaccine research ( 22 , 29 , 30 , 34 , 38 ). It was reported that immunization of piglets with the Δ waaJ or Δ waaL mutants of S. enterica ser.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been described that some LPS deficient mutants ( waaJ, waaL, rfaH, rfbH, rfbG, et al .) were used in Salmonella DIVA vaccine research ( 22 , 29 , 30 , 34 , 38 ). It was reported that immunization of piglets with the Δ waaJ or Δ waaL mutants of S. enterica ser.…”
Section: Discussionmentioning
confidence: 99%
“…Enteritidis and S. enterica ser. Pullorum S06004Δ spiC Δ waaL were also reported to have DIVA features ( 22 , 34 ). Our results showed that the antibodies produced by SG005Δ waaJ and SG005Δ waaJ Δ spiC did not react with S. enterica ser.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3c). Mutations in rfbG have been shown to cause a rough colony morphology and loss of LPS O antigen (32). During a screen for Salmonella genes required for long-term systemic infection after intraperitoneal infection, mutants in O-antigen biosynthesis were negatively selected (33).…”
Section: Discussionmentioning
confidence: 99%
“…These results were compared with wild type S. Pullorum S06004. The in vitro growth characteristics analysis of the mutant and wild-type strains was performed by measuring the optical density (OD 600 ) of each strain cultured in 20 mL of LB broth at 37°C with shaking at 180 rpm as previously described ( Jiao et al., 2017 ). The OD 600 was determined every hour and the monitoring was continued for 16 h. The LPS rough phenotype of the S06004 ΔspiCΔrfaH was identified by slide agglutination test using O 9 monoclonal antibody (O 9 MAb) developed in our laboratory and acriflavine (Sigma-Aldrich, MO, St. Louis, MO) agglutination test ( Jiao et al., 2018 ).…”
Section: Methodsmentioning
confidence: 99%